Potential Role of Whole Genome Sequencing to Predict the Virulence, Anti-TB Resistance, and Variants of Mycobacterium tuberculosis Strains from Rifampicin-sensitive Pulmonary Tuberculosis Patients in Surabaya, East Java, Indonesia - Ni Made Mertaniasih; Muhamad Frendy Setyawan; Ummi Amaliatush Sholichah Putri Merdekawati; Nurul Wiqoyah; Deby Kusumaningrum; Irfan Arif Ikhwani; Sohkichi Matsumoto (International Journal of Mycobacteriology)
Background: Tuberculosis (TB) is the second concern of a fatal infectious disease in the world caused by Mycobacterium tuberculosis (MTB). Indonesia has many regions that is known as a hotspot region for MTB cases, one of the most cities high newly case detected in 5 years was Surabaya. In 2022, Surabaya reported a higher pulmonary TB (PTB) prevalence rate of 0.35%. This study aimed to investigate the genomic and phylogenetic characteristics of MTB from isolates of rifampicin-sensitive PTB patients in Surabaya using whole genome sequencing (WGS). Methods: This study is a cross-sectional study to descriptively analyses WGS data using bioinformatics. Out of 8 enrolled drug-sensitive PTB patients; however, only three cultured isolates successfully grew on MB 7H11/OADC agar and subjected for WGS analysis. Results: Whole genome analysis revealed that all the samples were drug sensitive. The identified samples were majority belonged to lineage 4.4.1 (Euro-American [S-type]) and we found a novel strain in East Java region known as Lineage 4.10 (Euro-American [Uganda 1]). In addition, we identified a novel SNVs predicted to be associated with genomic adaptation in fgd1, embC, embA, and rv0565c under antibiotic pressures. Conclusion: WGS predicts that all the samples from pulmonary rifampicin-sensitive TB patients in this study were drug sensitive. We report the first discovery of a novel L4.10 strain, classified as Uganda 1, in Surabaya, Indonesia.